Cutaneous Manifestations of Antiphospholipid Syndrome: A Scoping Review - Alhammadi, Fatema Khaled; Alhammadi, Sara Khaled (Journal of Neonatal Surgery, 2025)
Background: Antiphospholipid Syndrome (APS) is a systemic autoimmune disorder characterized by vascular thrombosis and/or pregnancy morbidity in the presence of antiphospholipid antibodies. While its hematological and obstetric manifestations are well established, cutaneous manifestations are frequently overlooked despite their diagnostic and prognostic significance. The skin often provides early clinical clues that may precede systemic events, emphasizing the need for greater clinical awareness. Objective: This scoping review aims to explore, map, and synthesize existing literature on the spectrum of cutaneous manifestations associated with APS, elucidating their clinical presentations, diagnostic relevance, and implications for patient care. Methods: A systematic search was conducted across PubMed, Scopus, Web of Science, and Google Scholar databases, supplemented by manual screening of references. Studies were eligible if they discussed skin-related features in APS, were published in English, involved human participants, and provided primary or secondary data on dermatological findings. After duplicate removal and eligibility screening, 5 articles were selected from an initial pool of 354 studies. Reasons for exclusion included irrelevance to cutaneous features, non-availability of full texts, language barriers, or being non-peer-reviewed formats. Results: The review identified a range of cutaneous manifestations associated with APS, including but not limited to livedo reticularis, digital gangrene, skin ulcers, purpura, and necrotic lesions. Livedo reticularis emerged as the most commonly reported skin manifestation, often presenting as a chronic, non-inflammatory vascular pattern. In several cases, cutaneous signs were the initial clinical features that led to further diagnostic investigation for APS. The dermatologic findings were noted to correlate with both thrombotic risk and systemic involvement, particularly in cases of catastrophic APS (CAPS). Conclusion: Cutaneous manifestations play a critical role in the early detection and comprehensive management of APS. Recognizing these signs can aid clinicians in timely diagnosis, especially in patients without overt thrombotic or obstetric symptoms. Further research with standardized reporting and prospective designs is needed to strengthen clinical understanding of these manifestations and their prognostic implications.